Land use conflicts and livelihoods of small holder farmers in Ulanga district - Maksi, Deogratias Clemence (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirements for award of the Degree of Master of Science in Development Policy (MSc. DP) of Mzumbe University